1997
DOI: 10.1093/schbul/23.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Quit Using Substances Among Individuals With Schizophrenia: Implications for a Motivation-based Treatment Model

Abstract: Although the motivation to quit using substances is an important prognostic and treatment-matching factor in substance abuse treatment, there is limited information on motivation to quit among individuals with schizophrenia. This study used the five-stages-of-change model to evaluate the motivational levels of 497 individuals with schizophrenia or schizoaffective disorder in an outpatient mental health clinic. Rates of substance abuse, motivation levels to quit each specific substance, and correlates to motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
9

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(94 citation statements)
references
References 31 publications
3
82
0
9
Order By: Relevance
“…Even persons admitted to alcohol and drug treatment programs vary in their level of motivation for change (DiClemente & Hughes, 1990; Project Match Research Group, 1997). Consistent with these findings, when Ziedonis and Trudeau administered a staging algorithm to 224 outpatient dually diagnosed with schizophrenia-spectrum and substance use disorders, they found that 50% were in the precontemplation stage with respect to changing their substance use behavior; 2% were in contemplation stage; 8% in preparation; 4% in action; and 36% in maintenance (Ziedonis & Trudeau, 1997). Thus low levels of motivation for changing substance use behavior can be observed within a variety of treatment settings.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Even persons admitted to alcohol and drug treatment programs vary in their level of motivation for change (DiClemente & Hughes, 1990; Project Match Research Group, 1997). Consistent with these findings, when Ziedonis and Trudeau administered a staging algorithm to 224 outpatient dually diagnosed with schizophrenia-spectrum and substance use disorders, they found that 50% were in the precontemplation stage with respect to changing their substance use behavior; 2% were in contemplation stage; 8% in preparation; 4% in action; and 36% in maintenance (Ziedonis & Trudeau, 1997). Thus low levels of motivation for changing substance use behavior can be observed within a variety of treatment settings.…”
Section: Introductionmentioning
confidence: 76%
“…The cross-sectional nature of these data precludes inferences about temporal relations among these variables (i.e., the strong concurrent correlations observed among theoretically-related variables do not address the extent to which manipulating one might cause changes in another). Authors describing motivation enhancement interventions for this population have suggested that increasing a person's awareness of the cons of using, or the benefits of quitting, may result in greater recognition of substance use problems and likelihood of taking steps (Carey, 1996;Mercer, Mueser, & Drake, 1998;Ziedonis & Trudeau, 1997), however, longitudinal or experimental evidence for this relationship is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of unequivocal evidence for an efficient model for managing substance use in severe mental illness, motivational interviewing techniques, community reinforcement approaches, assertive case management, and a blend of standard psychological interventions for substance use with specific pharmacotherapies have each proven successful in extending abstinence (Ziedonis 1997;Brunette 2006a). …”
Section: How Successful Are These Models?mentioning
confidence: 99%
“…The intervention blends relapse prevention, social skills training, motivational enhancement therapy, and the "recovery language" of Twelve-Step Therapy 12,13 . In a number of trials, DRT has contributed to significant improvements in psychiatric and substance abuse outcomes and to better treatment adherence 12,14 . The DRT approach was not modified from the original format for the first six weeks of the TLC intervention.…”
Section: Dual Recovery Therapymentioning
confidence: 99%
“…The DRT approach was not modified from the original format for the first six weeks of the TLC intervention. This segment of DRT emphasized motivational enhancement techniques that promote treatment engagement and compliance to minimize the recidivism common among people with co-morbid disorders 12,14 . The remaining two weeks of the eight-week DRT component delivered through TLC is modified from the original format and focused on relapse prevention techniques and psycho-educational skills.…”
Section: Dual Recovery Therapymentioning
confidence: 99%